An Interreligious Tolerance in Warganet Condolence-expressions on Passing of B.J. Habibie: Anthropolinguistic Study - Laily Rahmatika; Agus Budi Wahyudi; Gallant Karunia Assidik (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
The passing of B.J. Habibie is identified as a form of utterance about the existence of interreligious tolerance in Indonesia. Interreligious is intersected with each other in upholding the value of tolerance as manifestation of a sense of Bhineka Tunggal Ika. The research aims to identify the value of tolerance based on potential diversities among interreligious in condolence-expressions. This type of research is a qualitative descriptive study. Data are from Warganet expressions which contain tolerance value. Collecting data uses purposive sampling technique. Data sources are taken from Warganet expressions on Twitter and Instagram. Analyzing data method uses distribution method with markup reading techniques and the equivalent method with referential equivalence technique that refers to the meaning outside of language. The result of this research is that interreligious tolerance is contained in the condolence-expressions in the form of expressions of religious, affection and kinship, and general.